Climate and Soil, Factors in the Control of Swollen Shoot Disease - Aboudou Karim Diallo; Walet Pierre N'Guessan; N’Dri Nobert Kouame; Kouakou Stanislas Koffi; Klotioloma Coulibaly; Francoise Gogbe-Dibi Bale; Aidara Sekou; Kouame Francois N'Guessan; Doumbia Mamadou (European Scientific Journal, ESJ, 2025)
Swollen shoot is a viral disease of the cocoa tree in the major cocoa-producing areas of West Africa. Its progression can be influenced by several factors, including climate and soil. This study aimed to assess the impact of mealybug vectors, climate and soil on the spread of swollen shoot disease in order to develop more effective control methods. It was done in the counties of Abengourou, Bouaflé, Divo and Soubré. Three plots showing early signs of infection were selected in each department. Thus, 6 concentric lines from a disease foci in different directions were defined and each line included 9 unaffected cocoa trees. These cocoa trees were tracked for 2 years. The data collection consisted of determining the number of diseased and dead trees as well as the number of colonies of mealybug species on each tagged cocoa plant. In addition, composite samples were taken in the 0–60 cm stratum of each plot to determine the texture, composition of organic matter and soil chemicals. Then, climate data, rainfall and temperature were collected over the observation period. The variance analysis indicated homogeneity between the dry and wet seasons, between clay-silt and clay-sandy soils, and between soils low in organic matter and those with acceptable organic matter, in terms of disease effects and mealybug populations. However, in the dry season, the Pearson correlation was significant between these variables in the departments. It was also significant between the level of sand, potassium (K+), magnesium (Mg2+), and exchangeable phosphorus contents, and the pH according to the textures studied and the soils poor in organic matter. Water deficit, soil texture, organic matter and nutrients of the cocoa tree are the factors that impact the spread of swollen shoot disease. These factors can therefore be used to implement an effective measure to combat swollen shoot disease.